(untitled) (International Journal of Architecture and Urbanism, 2020)
The theater usually has an attractive form to attract the attention of visitors and also has good sound control in the auditorium so as not to cause sound distortion. Performances in Medan are still inadequate to accommodate international performances. Particularly in Medan, the enthusiasm of the community towards art tends to be high, but the facilities of the place lack to accommodate performances. Data collection methods are carried out by collecting primary data through a process of field comparative study and secondary data through literature studies & comparative studies. The design approach used in design studies are analyzing the physical, conditions around the site, potential, the limits that exist on the site, Site and environmental approaches are analysis of site conditions and the best solutions, the user approach is building analysis to meet the need for facilities and quality in accommodating the show, literature studies related to titles and themes and theories that support design ideas. The Metaphor is chosen as a truss design theme to convey the shape of building design by combining metaphorical forms of buildings and the prominence of the same metaphorical theme in the building to those who visit and see buildings to prevent sound distortions by using porous materials. Medan is a big city in Indonesia as a design area with consideration of a strategic location. It is expected that with the presence of this performance center, domestic and foreign tourists and especially Medan people themselves can enjoy the comfort and get to know traditional music and dance in Indonesia.